Black women's mental health : balancing strength and vulnerability - Evans, Stephanie Y.; Bell, Kanika, 1976-; Burton, Nsenga K., 1972- (State University of New York Press, 2017)
"This book offers a unique, interdisciplinary, and thoughtful look at the challenges and potency of Black women's struggle for inner peace and mental stability. It brings together contributors from psychology, sociology, law, and medicine, as well as the humanities, to discuss issues ranging from stress, sexual assault, healing, self-care, and contemplative practice to health-policy considerations and parenting. Merging theory and practice with personal narratives and public policy, the book develops a new framework for approaching Black women's wellness in order to provide tangible solutions. The collection reflects feminist praxis and defines womanist peace in terms that reject both "superwoman" stereotypes and "victim" caricatures. Also included for health professionals are concrete recommendations for understanding and treating Black women"--Publisher's description